1997
DOI: 10.1161/01.cir.95.5.1328
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Nitric Oxide Synthesis Reduces Myocardial Oxygen Consumption In Vivo

Abstract: The blockade of NO synthesis reduces myocardial O2 consumption in vivo. The decrease in O2 consumption is accompanied by a decrease in segment shortening. It involves a direct myocardial action of NO, is unaffected by beta-blockade, and is consistent with in vitro studies indicating that low levels of NO augment contractile performance by inhibition of a cGMP-dependent phosphodiesterase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…In the normal as well as the failing human heart, endogenous and exogenous NO decreased myocardial tissue oxygen consumption (337,588). Suppression of NO production had previously been shown to increase myocardial oxygen consumption in awake dogs (38, 531), although this was not confirmed in other models (130,489,490,532). Inhibition of oxygen consumption by NO was documented also in noncontracting cardiac muscle slices (632).…”
Section: Autocrine and Paracrine Signaling From Cardiac Endothelial Cmentioning
confidence: 98%
“…In the normal as well as the failing human heart, endogenous and exogenous NO decreased myocardial tissue oxygen consumption (337,588). Suppression of NO production had previously been shown to increase myocardial oxygen consumption in awake dogs (38, 531), although this was not confirmed in other models (130,489,490,532). Inhibition of oxygen consumption by NO was documented also in noncontracting cardiac muscle slices (632).…”
Section: Autocrine and Paracrine Signaling From Cardiac Endothelial Cmentioning
confidence: 98%
“…These effects persist even when the effects of NO on blood flow are taken into account. However, NOS inhibitors do not always seem to increase myocardial oxygen consumption (42,49,68,76); the reasons for this discrepancy are not clear, although in some cases they are likely to relate to differences in the intracellular location, local concentration, permeability and K i of different inhibitors. Interestingly, no effect has been seen of NOS inhibitors on either oxygen consumption (44,69) or the redox state of cytochrome oxidase (30) in the anesthetized brain, even in the absence of potentially NO scavenging red blood cells (90).…”
Section: The Reality Of Inhibition?mentioning
confidence: 98%
“…1 Several investigators have reported that blockade of NO production with nonselective NO synthase (NOS) inhibitors leads to significant increases of myocardial oxygen consumption (MV O 2 ) in the normal heart, 2,3 although others found no effect 4 or a decrease in MV O 2 . 5 Three distinct NOS isoforms exist in mammalian cells: neuronal (nNOS), inducible (iNOS), and endothelial (eNOS) isoforms. 6 nNOS and eNOS are constitutively expressed in many cell types, whereas iNOS is expressed in response to infection, inflammation, or cytokine activation.…”
mentioning
confidence: 99%